Understanding adherence to international and national surgical site infection prevention guidelines in Saudi Arabia: A qualitative study - Alshahrani, Nouf (2025)
Background: The most common healthcare-associated infections are surgical site infections (SSIs). Worldwide, their incidence rate is approximately 20% to 38%, with rates in Saudi Arabia ranging from 10% to 86%. SSIs result in increased mortality and morbidity rates, increased healthcare costs and extended hospital stays. International and national SSI guidelines were developed to improve the quality of care and outcomes for surgical patients by providing standardized practices to prevent SSIs based on evidence. However, studies show that there is poor adherence to the SSI guidelines during the pre-and intraoperative periods among surgical team members worldwide. Moreover, there is a paucity of evidence concerning this topic in Saudi Arabia where there is a high incidence of SSIs. Aim: The aim of this study is to explore adherence to international and national SSI prevention guidelines by surgical team members during the pre-and intraoperative periods in Saudi Arabia.